2020
DOI: 10.3390/app10176049
|View full text |Cite
|
Sign up to set email alerts
|

Research on Longitudinal Collapse Mode and Control of the Continuous Bridge under Strong Seismic Excitations

Abstract: Bridge collapse events are common in major earthquakes around the world, among which continuous girder bridges are the most involved. In order to explore the collapse mechanism of a continuous girder bridge in an earthquake, the collapse mode of a two-span continuous girder bridge specimen which had been studied by the shaking table test was analyzed. Then, on the basis of the conventional plate rubber bearing system, the collapse control strategies which were high damping rubber bearing, fluid viscous damper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Hu et al [28] utilized ANSYS software to simulate the entire process of a model under earthquake loading, from stress analysis of concrete units to gradual failure of tower feet leading to instability of the bridge tower. Li et al [29] discussed control strategies for preventing collapse in cable-stayed bridges, including high-damping rubber bearings, fluid viscous dampers, and locking clutch control methods, and they demonstrated that these three collapse control methods can enhance the anti-collapse ability of bridge specimens while achieving a delayed collapse time, as desired. Ceravolo et al [30] successfully employed the Wiener entropy of strain measurements as a reliable tool to detect and assess multiple damages of varying sizes and severities in a buried steel pipeline model, demonstrating its viability.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [28] utilized ANSYS software to simulate the entire process of a model under earthquake loading, from stress analysis of concrete units to gradual failure of tower feet leading to instability of the bridge tower. Li et al [29] discussed control strategies for preventing collapse in cable-stayed bridges, including high-damping rubber bearings, fluid viscous dampers, and locking clutch control methods, and they demonstrated that these three collapse control methods can enhance the anti-collapse ability of bridge specimens while achieving a delayed collapse time, as desired. Ceravolo et al [30] successfully employed the Wiener entropy of strain measurements as a reliable tool to detect and assess multiple damages of varying sizes and severities in a buried steel pipeline model, demonstrating its viability.…”
Section: Introductionmentioning
confidence: 99%